Strengthening the Introduction of Indonesian – Bangkok History Through Collaboration with Payap University - Simanjuntak, Hotmaida; Pasaribu, Kondios Meidarlin; Siahaan, Monalisa Marta; Sirait, Gohima; br Tinambunan, Elizabeth (Journal Of Human And Education (JAHE), 2024)
This research aims to strengthen understanding of the history of relations between Indonesia and Bangkok through collaboration with Payap University. This collaboration involves various academic and cultural activities aimed at exploring, documenting and promoting the history of interactions between the two countries. The methods used in this research include literature study, interviews with historical experts, as well as participation in cultural and academic events organized by Payap University. The results of this collaboration show increased understanding and appreciation of the history of relations between Indonesia and Bangkok, as well as the formation of a stronger collaborative network between academic institutions from the two countries. This research also identified several challenges in the collaboration process, such as cultural and language differences, but these were offset by significant benefits in enriching historical knowledge and strengthening bilateral relations. It is hoped that this collaboration can become a model for similar efforts in the future, in order to strengthen international relations through academic and cultural approaches.